2020
DOI: 10.1186/s13567-020-00755-3
|View full text |Cite
|
Sign up to set email alerts
|

Akkermansia muciniphila protects intestinal mucosa from damage caused by S. pullorum by initiating proliferation of intestinal epithelium

Abstract: Akkermansia muciniphila, a novel mucin-degrading bacterium, has been demonstrated to prevent the development of obesity and related complications. However, whether it can protect poultry from intestinal mucosal damage by enteropathogens has never been mentioned. In this study, we found that A. muciniphila colonized in the intestine and then relieved intestinal mucosal damage in chicks caused by S. pullorum, including anatomical and morphological damage, alleviation of body weight and intestinal inflammation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 39 publications
4
30
0
1
Order By: Relevance
“…Previous studies reported that S. typhimurium secretes AvrA effector protein into host cells, therefore preventing the ubiquitination and degradation of β-catenin, which leads to the activation of Wnt/β-catenin pathway, accompanied with over-proliferation of intestinal cells and crypt hyperplasia in mice (39). The similar activation of Wnt/β-catenin pathway was also found in chickens with S. pullorum infection, as well as in mice with S. typhimurium infection (40,41). However, AvrA and SopB secreted by Salmonella activated Wnt signaling in intestinal M cells and crypt-localized epithelial cells, but inhibited Wnt signaling in intestinal epithelial cells (42).…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies reported that S. typhimurium secretes AvrA effector protein into host cells, therefore preventing the ubiquitination and degradation of β-catenin, which leads to the activation of Wnt/β-catenin pathway, accompanied with over-proliferation of intestinal cells and crypt hyperplasia in mice (39). The similar activation of Wnt/β-catenin pathway was also found in chickens with S. pullorum infection, as well as in mice with S. typhimurium infection (40,41). However, AvrA and SopB secreted by Salmonella activated Wnt signaling in intestinal M cells and crypt-localized epithelial cells, but inhibited Wnt signaling in intestinal epithelial cells (42).…”
Section: Discussionsupporting
confidence: 54%
“…Goblet cells, special intestinal epithelial cells in the gut, synthesize and secret mucins, such as Muc2, which are an important component of the intestinal mucosal barrier ( Yin et al, 2019 ). The current findings suggest that S. Typhimurium infection reduces the number of goblet cells, accompanied by downregulation of the mRNA expression levels of Muc2 and Tff2, which is also consistent with a previous report ( Zhu et al, 2020 ). However, Cu/Zn-Pal-1 addition may enhance the production of goblet cells and upregulate the mRNA expression of Muc2 and Tff2 in the CZPS group compared with the CON group.…”
Section: Discussionsupporting
confidence: 94%
“…2c ). Accordingly, both genera ( Corynebacterium and Akkermansia ) were more frequently found adherent to the mucosa than in stool samples ( 32 , 48 ). Besides these minor differences, all swabs contained highly similar microbiota.…”
Section: Resultsmentioning
confidence: 94%